Tingkat Kerawanan Kebakaran Hutan dan Lahan di Kecamatan Dusun Selatan Kabupaten Barito Selatan Kalimantan Tengah - Tangkasiang, Yos Andy (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
This study aims to analyze the level of vulnerability of forest and land fires in South Dusun District, South Barito Regency, Central Kalimantan Province. Dusun Selatan sub-district is an area that is vulnerable to the threat of forest and land fires every year, so mapping and analyzing the level of vulnerability is important to identify high-risk areas and develop appropriate mitigation strategies. This research uses a Geographic Information System (GIS) approach by considering several main factors, namely land cover, distance from roads, distance from rivers, slope, and soil type. Spatial and attribute data related to these factors were obtained from various sources and analyzed using overlay and weighting techniques. The mapping results show that most of the Dusun Selatan Sub-district area is safe from the risk of forest and land fires, covering around 59.09% or around 70,672.13 hectares of the total area. This information can be used by local governments and other stakeholders in the context of planning and decision-making related to the management and protection of forest areas, as well as the development of mitigation and preparedness strategies in facing the threat of forest and land fires in Dusun Selatan Sub-district.